Sodium ion battery and preparation method and application thereof

Through the technical solution of composited graphene with transition metal sulfide and introducing ion sieve functional layer and carbon-based nanofiber, the conductivity and interface stability of the positive electrode material of sodium ion battery are optimized, and the shortcomings of sodium ion battery in structural stability, interface chemical stability, sodium ion migration efficiency and thermal management capabilities are solved, and the effects of high energy density, good cycle stability and thermal stability are achieved.

CN119905645AActive Publication Date: 2025-04-29FUJIAN SHIJI HUANA NEW ENERGY TECHNOLOGY GROUP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510078471.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Sodium ion batteries have obvious shortcomings in the structural stability, interface chemical stability, sodium ion migration efficiency and thermal management capabilities of the positive electrode material, which limits the improvement of their performance.

Method used

Graphene is combined with transition metal sulfide, and ion sieve functional layer and carbon-based nanofiber are introduced. Through the modification and dispersion of functionalized graphene, the synthesis of transition metal sulfide, the introduction of ion sieve functional layer and the preparation of electrode sheets, the conductivity and interface stability of the positive electrode material are optimized, and a multi-dimensional thermal conductivity network is constructed to improve thermal management capabilities.

Benefits of technology

It significantly improves the energy density and rate performance of sodium ion batteries, improves cycle stability and thermal stability, solves the problems of easy attenuation and insufficient thermal management of traditional cathode materials, and enhances the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905645A_ABST
    Figure CN119905645A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage, and discloses a sodium ion battery which is a positive electrode material composed of the following components: graphene with the mass fraction of 5-20%; the mass fraction of the transition metal sulfide is 50%-70%; the invention discloses an ion sieve functional layer material, and also discloses a sodium ion battery preparation method, which comprises the following steps: graphene modification and dispersion: graphene powder is subjected to ultrasonic dispersion to form a suspension, and sodium persulfate and nitric acid are added to carry out functionalization treatment on the suspension; the transition metal sulfide is applied to portable electronic equipment, electric automobiles and large-scale energy storage systems. According to the invention, the functionalized graphene is compounded with the transition metal sulfide, and the multi-dimensional network design of the ion sieve functional layer and the carbon nanofiber is combined, so that the sodium ion transmission, conductivity and thermal management performance are optimized, and the energy density, the cycling stability and the safety are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a sodium ion battery and a preparation method and application thereof. Background Art

[0002] With the development of new energy technologies, the importance of energy storage systems in energy conversion and power regulation has become increasingly prominent. As a type of energy storage device with abundant resources, low cost and environmentally friendly characteristics, sodium-ion batteries have gradually attracted the attention of researchers. However, compared with lithium-ion batteries, the maturity of sodium-ion battery technology is still low, and there are significant deficiencies in key performance such as energy density, cycle life and operational safety.

[0003] Currently, the positive electrode materials of sodium-ion batteries mostly use active materials such as metal oxides and metal sulfides. However, due to the large ionic radius of sodium ions, they can easily cause the material structure to expand or collapse during the embedding and de-embedding process. After long-term cycling, the positive electrode materials often become powdery, resulting in a rapid decay of the battery capacity. In addition, traditional positive electrode materials are also weak in electron transmission capabilities, which limits the battery's discharge capacity under high-rate conditions. These problems are common in sodium-ion batteries, limiting their performance improvements.

[0004] At the same time, the interfacial reaction between the electrolyte and the electrode of the sodium-ion battery also has an important impact on the performance. Due to the low migration rate of sodium ions, side reaction products are easily formed at the interface during the cycle, which significantly increases the impedance. This phenomenon is particularly obvious during high-rate charge and discharge and long-term cycling, further reducing the utilization efficiency of sodium ions. In addition, the instability of the electrolyte may also lead to the formation of sodium dendrites, which not only shortens the service life of the battery, but also significantly increases the safety risk.

[0005] The thermal stability of sodium-ion batteries also needs to be addressed. Under high-rate charge and discharge or high-temperature conditions, local heat accumulation is more serious, which can easily lead to interface failure, material degradation, and even thermal runaway. Although some studies have tried to introduce thermal conductive materials or optimize electrolytes to alleviate thermal management issues, these solutions often have difficulty balancing conductivity and stability, resulting in poor overall battery performance.

[0006] In summary, sodium-ion batteries have obvious shortcomings in terms of structural stability of positive electrode materials, interfacial chemical stability, sodium ion migration efficiency, and thermal management capabilities. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a sodium ion battery and a preparation method and application thereof, which solve the technical problems of sodium ion batteries in terms of conductivity of positive electrode materials, interface stability, sodium ion migration efficiency and thermal management performance.

[0008] To achieve the above objectives, the present invention is implemented by the following technical solutions: A sodium ion battery, comprising: A positive electrode material consisting of: Graphene, mass fraction is 5%-20%; Transition metal sulfides, mass fraction is 50%-70%; Ion sieve functional layer material, mass fraction is 5%-15%; Carbon-based nanofibers, with a mass fraction of 5%-10%; Binder, mass fraction is 3%-5%; Sodium metal anode; The electrolyte is a solution of NaClO4 dissolved in EC and DMC solvents, the solvent volume ratio is 1:1, and the concentration is 0.5-1M.

[0009] Preferably, the transition metal sulfide includes one or more of nickel sulfide, cobalt sulfide, iron sulfide or vanadium sulfide.

[0010] Preferably, the ion sieve functional layer material is a metal organic framework, including ZIF-8 or its derivative materials.

[0011] Preferably, the graphene is functionalized graphene modified by oxidation, and contains hydroxyl and carboxyl groups on the surface.

[0012] Preferably, the carbon-based nanofibers are carbon nanotubes, and the carbon nanotubes are compounded with the positive electrode material by mechanical mixing.

[0013] A method for preparing a sodium ion battery comprises the following steps: Modification and dispersion of graphene: Graphene powder is dispersed by ultrasound to form a suspension, and sodium persulfate and nitric acid are added to functionalize it; Synthesis of transition metal sulfides: The functionalized graphene suspension is mixed with a precursor solution containing a transition metal salt and a sulfur source, and the composite material is synthesized by a high-temperature solid-phase reaction under inert gas protection; Introduction of ion sieving functional layer: Mixing transition metal sulfide composite material with MOF precursor to form ion sieving functional layer through solvothermal reaction; Preparation of electrode sheet: The composite material is mixed with carbon-based nanofibers, a binder and a conductive agent into a slurry, coated on a current collector, and pressed into a sheet after drying to form a positive electrode sheet; Battery assembly: Assemble the positive electrode, sodium metal negative electrode and electrolyte into a sodium ion battery Preferably, the treatment temperature of the functionalized graphene suspension is 50° C.-80° C., and the treatment time is 2-3 h.

[0014] Preferably, the temperature of the high temperature solid phase reaction is 300°C-400°C, and the time is 4-6h.

[0015] Preferably, the temperature of the solvent thermal reaction is 150°C-200°C, and the time is 6-12h.

[0016] The sodium ion battery is applied to portable electronic devices, electric vehicles and large-scale energy storage systems.

[0017] The present invention provides a sodium ion battery and a preparation method and application thereof, which have the following beneficial effects: 1. The present invention adopts a technical solution of graphene and transition metal sulfide composite and introduces an ion sieve functional layer. It realizes efficient sodium ion transmission and conductive network optimization. Compared with the problem of insufficient conductivity caused by a single active material in the prior art, it significantly improves the energy density and rate performance of the battery and solves the problem of easy attenuation of traditional positive electrode materials.

[0018] 2. The present invention constructs an ion sieving functional layer on the surface of the composite material through a solvothermal method, accurately screens sodium ions and inhibits side reactions, effectively reducing the capacity loss of the battery in multiple charge and discharge cycles. Compared with the solution in the prior art that does not optimize the interface structure, it greatly improves the cycle stability and overcomes the technical defect of serious interface side reactions.

[0019] 3. The present invention adds carbon nanofibers to the positive electrode to construct a multi-dimensional thermal and electrical conductive network, while optimizing material distribution and thermal management capabilities, thereby achieving stability under high-rate charge and discharge conditions. Compared with the safety hazards caused by insufficient thermal management in the prior art, the present invention improves the thermal stability and safety performance of the battery and solves the problem of thermal runaway in extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Please see attached Figure 1 , an embodiment of the present invention provides a sodium ion battery, comprising: A positive electrode material consisting of: Graphene, mass fraction is 5%-20%; Transition metal sulfides, mass fraction is 50%-70%; Ion sieve functional layer material, mass fraction is 5%-15%; Carbon-based nanofibers, with a mass fraction of 5%-10%; Binder, mass fraction is 3%-5%; Sodium metal anode; Electrolyte: The electrolyte is a solution of NaClO4 dissolved in EC and DMC solvents, with a solvent volume ratio of 1:1 and a concentration of 0.5-1M.

[0023] The transition metal sulfide includes one or more of nickel sulfide, cobalt sulfide, iron sulfide or vanadium sulfide.

[0024] The material of the ion sieve functional layer is a metal organic framework, including ZIF-8 or its derivative materials.

[0025] Graphene is functionalized graphene that has been oxidatively modified and contains hydroxyl and carboxyl groups on its surface.

[0026] The carbon-based nanofibers are carbon nanotubes, which are compounded with the positive electrode material by mechanical mixing.

[0027] A method for preparing a sodium ion battery comprises the following steps: Modification and dispersion of graphene: Graphene powder is dispersed by ultrasound to form a suspension, and sodium persulfate and nitric acid are added to functionalize it; Synthesis of transition metal sulfides: The functionalized graphene suspension is mixed with a precursor solution containing a transition metal salt and a sulfur source, and the composite material is synthesized by a high-temperature solid-phase reaction under inert gas protection; Introduction of ion sieving functional layer: Mixing transition metal sulfide composite material with MOF precursor to form ion sieving functional layer through solvothermal reaction; Preparation of electrode sheet: The composite material is mixed with carbon-based nanofibers, a binder and a conductive agent into a slurry, coated on a current collector, and pressed into a sheet after drying to form a positive electrode sheet; Battery assembly: Assemble the positive electrode, sodium metal negative electrode and electrolyte into a sodium-ion battery.

[0028] The processing temperature of the functionalized graphene suspension is 50° C.-80° C., and the processing time is 2-3 hours.

[0029] The temperature of the high temperature solid phase reaction is 300°C-400°C, and the time is 4-6h.

[0030] The temperature of the solvent thermal reaction is 150°C-200°C, and the time is 6-12h.

[0031] A sodium ion battery is used in portable electronic devices, electric vehicles and large-scale energy storage systems.

[0032] Example 1: Preparation of positive electrode materials with nickel sulfide as the core and battery assembly Graphene modification and dispersion: 10 g of high-purity graphene was added into 200 mL of deionized water and ultrasonically dispersed for 30 min (power 400 W) to form a suspension.

[0033] Add 2 g of sodium persulfate and 5 mL of nitric acid, maintain the temperature at 70°C, and stir for 2 h.

[0034] After centrifugal separation, the product was washed three times with deionized water and dried to obtain functionalized graphene.

[0035] Transition Metal Sulfide Synthesis: Take 5 g of functionalized graphene and add it to 50 mL of nickel nitrate (0.1 M) and 25 mL of thiourea (0.05 M) solution.

[0036] After uniform stirring, the temperature was raised to 350°C under argon protection and maintained for 4 h.

[0037] After cooling, washing and vacuum drying for 24 hours, a graphene-nickel sulfide composite material was obtained.

[0038] Introducing ion sieving functional layer: 2 g of the composite material was mixed with 50 mL of ethanol solution containing ZIF-8 precursor.

[0039] The composite material with a functional layer was obtained by solvent thermal reaction at 150°C for 8 hours.

[0040] Wash again and dry for later use.

[0041] Electrode preparation: 7 g of composite material, 2 g of carbon nanotubes and 1 g of binder were mixed, and an appropriate amount of NMP was added and stirred for 6 h to prepare a slurry.

[0042] The slurry is coated on copper foil, dried and pressed into sheets to make positive electrode sheets.

[0043] Battery Assembly: The positive electrode sheet, sodium metal anode and NaClO4-EC / DMC (1M) electrolyte were assembled into a button cell in a glove box.

[0044] The cycle performance was tested using constant current charge and discharge.

[0045] Example 2: Fast-charging sodium-ion battery based on cobalt sulfide Preparation of functionalized graphene suspension: Take 15g of graphene and add it into 300mL of water, with ultrasonic power of 300W and treat for 45min.

[0046] Add 1 g of sodium persulfate and 3 mL of nitric acid and react at 60°C for 3 h.

[0047] After centrifugal separation and drying, oxidized modified graphene is obtained.

[0048] Synthesis of Cobalt Sulfide Composites: Prepare 100 mL of 0.2 M cobalt nitrate solution, add 10 g of functionalized graphene and 20 mL of sodium sulfide (0.1 M).

[0049] The reaction was carried out at 400°C under argon protection for 6 hours to generate a graphene-cobalt sulfide composite material.

[0050] MOF functional layer modification: The ZIF-8 precursor was dissolved in ethanol, added to the composite material, and subjected to solvent thermal reaction at 120°C for 10 h.

[0051] After drying, a complete structural material is obtained.

[0052] Electrode sheet preparation and battery assembly: 6 g of composite material, 3 g of carbon nanofiber and 1 g of conductive carbon black were mixed, coated with copper foil, dried and pressed into electrode sheets.

[0053] The negative electrode used a sodium metal sheet and the electrolyte used NaClO4 (0.5M).

[0054] Assemble the button cell battery.

[0055] Example 3: High-safety sodium-ion battery based on iron sulfide Functionalized graphene preparation: 20 g of graphene was added into 500 mL of water, and the ultrasonic power was 500 W for 30 min.

[0056] Add 3 g of sodium persulfate, maintain the temperature at 50°C, and stir for 1.5 h.

[0057] Wash by centrifugation and dry for later use.

[0058] Preparation of Iron Sulfide: Take 5 g of functionalized graphene and mix it with FeCl3 solution (0.1 M, 50 mL) and sodium sulfide (0.05 M, 25 mL).

[0059] The temperature was raised to 300°C under argon protection and maintained for 5 hours to generate a graphene-iron sulfide composite material.

[0060] Functional layer and carbon fiber introduction: A ZIF-8 precursor (mass ratio 1:1) was added to the composite material, and a solvothermal reaction was carried out at 150° C. for 6 h.

[0061] Then add carbon nanofibers and mix in proportion to form a complete positive electrode material.

[0062] Electrode and battery assembly: The positive electrode slurry is coated on aluminum foil and dried to prepare an electrode sheet.

[0063] Sodium metal anode, electrolyte is NaClO4 (1M) dissolved in EC / DMC.

[0064] Assemble into button battery.

[0065] Example 4: Energy storage system battery with vanadium sulfide as the core Functionalized graphene preparation: In an environment of 60°C, 10 g of graphene was added to 200 mL of water and ultrasonicated for 40 min.

[0066] 2 g of sodium persulfate was added, reacted for 2 h, and then centrifuged and dried to obtain modified graphene.

[0067] Vanadium sulfide synthesis: NH4VO3 (10 g) was mixed with thiourea (5 g) and stirred evenly in the graphene suspension.

[0068] The reaction was carried out at 400°C in an inert atmosphere for 4 hours to obtain a graphene-vanadium sulfide composite material.

[0069] Functional layer construction and electrode preparation: The functional layer was modified by ZIF-8 and solvent thermally treated at 150°C for 6 h.

[0070] Carbon nanotubes are added to form a composite positive electrode slurry, which is then coated on a current collector and dried and pressed into sheets.

[0071] Battery assembly and testing: The positive electrode, sodium metal negative electrode and NaClO4 electrolyte are assembled into button cells for high current charge and discharge performance testing.

[0072] Comparative Example 1: Graphene is not functionalized Corresponding Example: Example 1 (positive electrode material with nickel sulfide as the core) Graphene dispersion: Unfunctionalized graphene was used directly, 10 g was added into 200 mL of deionized water, and ultrasonic dispersion was performed for 30 min (power 400 W).

[0073] No sodium persulfate or nitric acid treatment was performed.

[0074] Synthesis of transition metal sulfides: Untreated graphene was mixed with nickel nitrate (0.1 M, 50 mL) and thiourea (0.05 M, 25 mL), heated to 350 °C under argon protection and maintained for 4 h to generate graphene-nickel sulfide composite materials.

[0075] Subsequent steps: Maintain the same ion sieve functional layer introduction, electrode sheet preparation and battery assembly process as in Example 1.

[0076] Comparative Example 2: No ion sieve functional layer Corresponding Example: Example 2 (positive electrode material with cobalt sulfide as the core) Preparation of functionalized graphene: 15 g of graphene was taken and functionalized according to the method of Example 2.

[0077] Synthesis of cobalt sulfide composite material: According to the method of Example 2, functionalized graphene was reacted with cobalt nitrate (0.2 M, 100 mL) and sodium sulfide (0.1 M, 20 mL) at 400° C. under argon for 6 h.

[0078] Use of composite materials without functional layers: No ZIF-8 functional layer modification is introduced, and the graphene-cobalt sulfide composite material is directly used to prepare the positive electrode slurry.

[0079] Subsequent steps: electrode sheet preparation and battery assembly are consistent with Example 2.

[0080] Comparative Example 3: No carbon-based nanofibers added Corresponding Example: Example 3 (positive electrode material with iron sulfide as the core) Preparation of functionalized graphene: refer to the functionalization treatment method of Example 3.

[0081] Synthesis of iron sulfide composites: Functionalized graphene was mixed with FeCl3 solution (0.1 M, 50 mL) and sodium sulfide (0.05 M, 25 mL) and reacted in an argon environment at 300 °C for 5 h.

[0082] No carbon-based nanofibers: When preparing the positive electrode slurry, only 7 g of the composite material, 1 g of the binder and 2 g of the conductive carbon black were used, and no carbon-based nanofibers were added.

[0083] Subsequent steps: The other steps are consistent with Example 3, including electrode sheet preparation and battery assembly.

[0084] Comparative Example 4: Traditional electrolyte system (no optimization) Corresponding Example: Example 4 (Energy storage system battery with vanadium sulfide as the core) Functionalized graphene preparation: the same functionalization treatment as in Example 4.

[0085] Synthesis of vanadium sulfide composite material: NH4VO3 (10 g) and thiourea (5 g) were mixed in a graphene suspension and reacted at 400°C for 4 h according to the method of Example 4 to prepare a vanadium sulfide composite material.

[0086] Traditional electrolyte system: The electrolyte is NaPF6 (1M) dissolved in EC / DMC (1:1) solvent, and the optimized NaClO4 system is not used.

[0087] Subsequent steps: The electrode sheet preparation and battery assembly process are consistent with Example 4.

[0088] Comparative Example 5: Using unmodified graphene and a single active material Corresponding Example: Example 1 (positive electrode material with nickel sulfide as the core) Combination of graphene and nickel sulfide: No functionalized graphene was used. Only 10 g of ordinary graphene powder was mixed with 0.1 M nickel nitrate solution and reacted without a sulfide precursor.

[0089] Single nickel sulfide active material: The prepared positive electrode material contains only nickel sulfide and no graphene composite network.

[0090] Subsequent steps: Keep the electrode sheet preparation and battery assembly consistent with Example 1.

[0091] Experiment 1: Battery Cycle Performance Test Experimental description: Experimental purpose: To verify the energy density and cycle performance advantages of the technical solution of the present invention using functionalized graphene and ion sieve functional layer materials in sodium ion batteries.

[0092] Experimental equipment: constant current and constant voltage charge and discharge tester, battery fixture, button battery test stand.

[0093] Experimental Materials: Example 1 (Functionalized graphene + nickel sulfide + ion sieve functional layer) Comparative Example 1 (unfunctionalized graphene) Comparative Example 2 (without ion sieve functional layer) Experimental steps: Sample preparation: Button batteries were prepared according to the descriptions of Example 1, Comparative Example 1 and Comparative Example 2, respectively, to ensure that the positive electrode sheet, electrolyte and negative electrode sheet were assembled completely and correctly.

[0094] Charge and discharge cycle: Install the assembled button cell on the test stand.

[0095] Set the constant current charge and discharge mode, the current density is 0.5C, and the charge and discharge voltage range is 2.0V to 4.2V.

[0096] The cycle test was performed 500 times, and the discharge capacity and coulombic efficiency of each cycle were recorded.

[0097] Data recording and processing: Measure and record the initial capacity of each battery, the remaining capacity after each cycle, and the capacity retention rate during the cycle test.

[0098] The change in Coulombic efficiency was recorded for each cycle.

[0099] Experimental data: Table 1: Comparison of cycle test results (Example 1 and Comparative Example) Cycle times Example 1 Capacity (mAh / g) Comparative Example 1 Capacity (mAh / g) Comparative Example 2 Capacity (mAh / g) Initial Value 145.3 122.5 133.8 50 140.6 109.3 120.1 100 138.9 98.7 112.5 150 135.7 91.4 102.8 200 132.5 85.9 93.4 300 128.4 76.3 81.9 400 122.9 68.7 72.3 500 120.2 62.5 65.1 Summary: The results of the cycling performance tests show significant differences. The use of functionalized graphene in the positive electrode is clearly the key. Its high conductivity and the binding force of the modified surface hydroxyl and carboxyl groups make nickel sulfide more stable during charge and discharge. The ion sieve functional layer further optimizes the interface transmission and reduces the side reactions caused by electrolyte decomposition. This combination allows the battery to maintain a high capacity over a long period of cycling, while the control ratio shows significant degradation due to the lack of such a design.

[0100] From another perspective, the use of unfunctionalized graphene limits the electron migration rate of the positive electrode material. The results show that the initial capacity of the battery is low and the capacity decays faster during the cycle. This shows that the functionalization of graphene not only improves the conductive network, but also improves the distribution uniformity of the active material, avoiding the problem of excessive local current density. The lack of the ion sieving functional layer enhances the side reactions of the electrolyte, further reducing the cycle stability.

[0101] Furthermore, as the number of cycles increases, the difference in coulombic efficiency begins to emerge. Batteries without ion sieve functional layers have poor sodium ion migration selectivity, resulting in an increase in side reaction products, which affects the long-term capacity retention rate. It can be said that the synergy of positive electrode material design is the core path to solving the problem of sodium ion battery cycle stability. This synergy is achieved through the joint efforts of functionalized graphene, transition metal sulfides and ion sieve functional layers, which is unmatched by traditional designs.

[0102] Experiment 2: Rate performance test Experimental description: Experimental purpose: To test the sodium ion transmission efficiency and conductive network stability of the present invention under high rate charge and discharge conditions. By comparing with the comparative example, the effect of functionalized graphene and carbon-based nanofibers on improving rate performance was verified.

[0103] Experimental equipment: electrochemical workstation, constant current and constant voltage charge and discharge tester, battery fixture and test stand.

[0104] Experimental Materials: Example 2 (Functionalized graphene + cobalt sulfide + carbon-based nanofibers) Comparative Example 3 (without carbon-based nanofibers) Comparative Example 5 (Unmodified Graphene and Single Cobalt Sulfide) Experimental steps: Sample preparation: Button cells were prepared according to the processes of Example 2, Comparative Example 3 and Comparative Example 5 to ensure the quality consistency of the positive electrode sheet, electrolyte and negative electrode sheet.

[0105] Rate performance test: Install the button cell on the test stand and connect it to the electrochemical workstation.

[0106] Set the constant current charge and discharge mode, and gradually increase the current density: 0.5C (low rate), 1C, 2C, 5C, 10C (high rate).

[0107] Three charge and discharge cycles were performed at each rate, and the discharge specific capacity and Coulombic efficiency were recorded.

[0108] Continue testing for 10 cycles at 10C to observe the capacity change trend.

[0109] Data Records: The discharge capacity and coulombic efficiency changes at each rate were measured and recorded.

[0110] Analyze the differences in capacity retention under different rate conditions.

[0111] Experimental data: Table 2: Comparison of specific capacity and efficiency under different rate conditions Current density (C) Example 2 Specific capacity (mAh / g) Comparative Example 3 Specific Capacity (mAh / g) Comparative Example 5 Specific Capacity (mAh / g) 0.5 137.6 122.4 109.8 1 132.1 115.7 97.5 2 125.8 106.3 85.1 5 110.2 89.7 62.5 10 92.4 73.2 45.8 10 (10 cycles) 88.6 66.8 40.2 Summary: Under high rate conditions, the performance difference of the battery is immediately apparent. The functionalized graphene of the present invention provides a highly uniform conductive network, while the addition of carbon-based nanofibers enhances the transmission efficiency of electrons and ions. This multidimensional conductivity is obviously crucial for high rate charging and discharging. Comparative Example 3 lacks the support of carbon-based nanofibers, the electrochemical polarization increases, and the capacity drops rapidly after the rate is increased. To make matters worse, because Comparative Example 5 uses unmodified graphene, the active material is unevenly distributed, the sodium ion transmission path is limited, and it is almost impossible to maintain reasonable performance at high rates.

[0112] When the current density increases, the lack of transmission efficiency will amplify the interface problem. The ion migration path of Example 2 is obviously optimized. The introduction of polar groups on the surface of functionalized graphene stabilizes the structure of the sulfide, so that it will not undergo obvious structural collapse during rapid charge and discharge. However, Comparative Example 5 shows that the diffusion of sodium ions inside the material is significantly hindered, resulting in a serious lack of utilization of the active area. This problem is particularly prominent at high rates.

[0113] In addition, the role of carbon-based nanofibers is not only to provide additional conductive paths. After continuous cycling at 10C, the capacity of Example 2 can still remain stable, while the capacity decay of Comparative Example 3 is very obvious. This shows that the high thermal conductivity of carbon fiber significantly improves the problem of local heat accumulation in the electrode. This thermal management advantage plays an irreplaceable role in practical high-rate applications, especially in portable electronic devices and energy storage systems.

[0114] Experiment 3: Thermal stability test Experimental description: Experimental purpose: To verify the effect of improving the thermal stability and cycle performance of sodium ion batteries in high temperature environments through the multi-dimensional thermal conductive network design of the ion sieve functional layer and carbon-based nanofibers in the present invention.

[0115] Experimental equipment: constant temperature box, constant current and constant voltage charge and discharge tester, thermal imager.

[0116] Experimental Materials: Example 3 (Functionalized graphene + iron sulfide + ion sieve functional layer + carbon-based nanofiber) Comparative Example 2 (without ion sieve functional layer) Comparative Example 4 (Unoptimized Electrolyte System) Experimental steps: Sample preparation: Button batteries were prepared according to Example 3, Comparative Example 2 and Comparative Example 4, respectively, to ensure the consistency of battery assembly.

[0117] Thermal stability test: Place button cells in the following two environments: Room temperature (25°C); High temperature (80℃, in constant temperature box).

[0118] Set the constant current charge and discharge conditions: 0.5C current density, voltage range 2.0V to 4.2V.

[0119] Under each environment, 100 charge and discharge cycles were performed, and the discharge capacity and capacity retention rate were recorded.

[0120] Use a thermal imager to monitor the surface temperature distribution of each battery in a high-temperature environment and record the thermal management performance.

[0121] Data recording and analysis: Analyze the discharge capacity, capacity retention and thermal distribution under high temperature conditions, and compare the differences in battery stability.

[0122] Experimental data: Table 3: Thermal stability test results under different conditions Cycle times Ambient temperature Example 3 Capacity (mAh / g) Comparative Example 2 Capacity (mAh / g) Comparative Example 4 Capacity (mAh / g) Initial Value Room temperature 138.5 122.7 128.3 25 Room temperature 134.3 114.8 119.6 50 Room temperature 129.8 108.5 113.2 100 Room temperature 124.7 99.3 102.4 Initial Value 80℃ 137.4 121.5 127.6 25 80℃ 128.6 99.8 107.5 50 80℃ 122.4 86.2 91.8 100 80℃ 117.9 75.6 80.3 Summary: Under high temperature conditions, the thermal stability of the battery becomes a key issue. Experiments show that Example 3 performs significantly better than the comparative example. The synergistic effect of functionalized graphene and iron sulfide improves the interface stability, while the ion sieve functional layer reduces the gas generated by side reactions. This design reduces the risk of thermal runaway, allowing the battery to maintain a stable capacity at high temperatures. Due to the lack of an ion sieve functional layer, the interface side reactions in Comparative Example 2 are more serious, and the capacity drops rapidly in a high temperature environment.

[0123] In addition, the introduction of carbon-based nanofibers plays a vital role in thermal management. Thermal imaging data show that the temperature distribution of Example 3 is more uniform, and the local overheating phenomenon is significantly reduced. In contrast, in Comparative Example 4, under the unoptimized electrolyte system, the interface impedance increases and the heat accumulation problem becomes more prominent. In the long run, this thermal management capability plays a key protective role in the safety and life of the battery in a high temperature environment.

[0124] Fundamentally, the stability of Example 3 stems from the synergy of material design. Functionalized graphene enhances the dispersibility and conductivity of the positive electrode material, the ion sieve functional layer optimizes the sodium ion migration channel, and the carbon-based nanofibers provide additional thermal conductivity paths. This multi-dimensional collaborative design is not achievable with traditional single optimization strategies. The experimental results further prove that the technical solution of the present invention can achieve stable and reliable performance in high-temperature energy storage scenarios and is suitable for energy storage applications under complex working conditions.

[0125] Experiment 4: Large-scale energy storage simulation test Experimental description: Purpose of the experiment: To simulate the application scenario of sodium-ion batteries in large-scale energy storage systems, and to verify the performance advantages of the present invention in long-term operation by testing energy efficiency and stability.

[0126] Experimental equipment: constant current discharge simulation system, battery constant current charging device, simulated energy storage load (50W), temperature monitoring module.

[0127] Experimental Materials: Example 4 (Functionalized graphene + vanadium sulfide + ion sieve functional layer + optimized electrolyte system) Comparative Example 4 (Unoptimized Electrolyte System) Comparative Example 5 (Single Vanadium Sulfide + Unmodified Graphene) Experimental steps: Sample preparation: Button cells were prepared according to the processes of Example 4, Comparative Example 4 and Comparative Example 5, respectively.

[0128] Energy storage simulation test: Connect each battery group to a simulated energy storage load and set constant current charging and constant power discharging cycle conditions: Constant current charging current density: 0.5C.

[0129] Discharge power: 50W.

[0130] The system was operated for 72 hours, and the energy efficiency, capacity retention rate and surface temperature changes during operation were recorded.

[0131] Data recording and processing: The battery’s discharge capacity, energy efficiency and temperature fluctuations are recorded every hour.

[0132] Compare the long-term performance of different samples in simulated energy storage applications.

[0133] Experimental data: Table 4: Comparison of energy storage simulation test results Time (h) Example 4 Energy Efficiency (%) Comparative Example 4 Energy Efficiency (%) Comparative Example 5 Energy Efficiency (%) 1 91.5 87.2 83.6 6 90.8 83.5 78.2 12 89.7 80.1 73.4 24 87.3 76.8 69.7 36 85.9 72.3 64.5 48 84.5 68.9 59.8 60 83.1 64.7 55.3 72 82.4 60.2 50.9 Summary: In the simulation test of the energy storage system, the pros and cons of performance quickly became apparent. The performance of Example 4 is obviously advantageous, and the optimized electrolyte system effectively improves the migration rate and interface stability of sodium ions. Combined with functionalized graphene and ion sieve functional layers, this design significantly improves the energy efficiency, which remains above 80% after 72 hours of operation. However, because the impedance of the unoptimized electrolyte in Comparative Example 4 is higher, the energy loss is significantly increased, resulting in a rapid decrease in efficiency. As for Comparative Example 5, its combination of a single active material and unmodified graphene hinders the migration of sodium ions, resulting in low efficiency and faster decay.

[0134] The test results of temperature fluctuations are more intuitive. The thermal management design of Example 4 benefits from the multi-dimensional heat conduction network of carbon-based nanofibers, and the temperature change on the battery surface remains uniform when the load fluctuates. In contrast, the temperature rise in Comparative Example 4 is more dramatic, and local hot spots are obvious. Comparative Example 5 of unmodified graphene further exposes its weakness under high load conditions, with severe heat accumulation and difficulty in dissipation, showing potential safety hazards.

[0135] From a mechanistic analysis, the design of the present invention is the result of multi-level collaboration. Optimizing the electrolyte reduces the interfacial impedance and improves the transmission rate of sodium ions; the high conductivity and stability of functionalized graphene provide good support for the positive electrode; the ion sieve functional layer accurately screens sodium ions and reduces side reactions. In addition, the thermal management function of carbon-based nanofibers is indispensable, and this material collaborative design provides a more reliable performance guarantee for the energy storage system. Experimental results show that the present invention has significant advantages in actual application scenarios and is an ideal choice for large-scale energy storage.

[0136] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A sodium ion battery, characterized in that: include: A positive electrode material consisting of: Graphene, mass fraction is 5%-20%; Transition metal sulfides, mass fraction is 50%-70%; Ion sieve functional layer material, mass fraction is 5%-15%; Carbon-based nanofibers, with a mass fraction of 5%-10%; Binder, mass fraction is 3%-5%; Sodium metal anode; The electrolyte is a solution of NaClO4 dissolved in EC and DMC solvents, the solvent volume ratio is 1:1, and the concentration is 0.5-1M.

2. A sodium ion battery according to claim 1, characterized in that: The transition metal sulfide includes one or more of nickel sulfide, cobalt sulfide, iron sulfide or vanadium sulfide.

3. A sodium ion battery according to claim 1, characterized in that: The ion sieve functional layer material is a metal organic framework, including ZIF-8 or its derivative materials.

4. A sodium ion battery according to claim 1, characterized in that: The graphene is functionalized graphene modified by oxidation, and contains hydroxyl and carboxyl groups on the surface.

5. A sodium ion battery according to claim 1, characterized in that: The carbon-based nanofibers are carbon nanotubes, and the carbon nanotubes are compounded with the positive electrode material by a mechanical mixing method.

6. A method for preparing a sodium ion battery, characterized in that: The following steps are involved: Modification and dispersion of graphene: Graphene powder is dispersed by ultrasound to form a suspension, and sodium persulfate and nitric acid are added to functionalize it; Synthesis of transition metal sulfides: The functionalized graphene suspension is mixed with a precursor solution containing a transition metal salt and a sulfur source, and the composite material is synthesized by a high-temperature solid-phase reaction under inert gas protection; Introduction of ion sieving functional layer: Mixing transition metal sulfide composite material with MOF precursor to form ion sieving functional layer through solvothermal reaction; Preparation of electrode sheet: The composite material is mixed with carbon-based nanofibers, a binder and a conductive agent into a slurry, coated on a current collector, and pressed into a sheet after drying to form a positive electrode sheet; Battery assembly: Assemble the positive electrode, sodium metal negative electrode and electrolyte into a sodium-ion battery.

7. A method for preparing a sodium ion battery according to claim 6, characterized in that: The processing temperature of the functionalized graphene suspension is 50° C.-80° C., and the processing time is 2-3 hours.

8. A method for preparing a sodium ion battery according to claim 6, characterized in that: The temperature of the high temperature solid phase reaction is 300° C.-400° C., and the time is 4-6 hours.

9. The method for preparing a sodium ion battery according to claim 6, wherein the temperature of the solvent thermal reaction is 150°C-200°C, and the time is 6-12 hours.

10. A sodium ion battery according to any one of claims 1 to 5, characterized in that: Used in portable electronic devices, electric vehicles and large-scale energy storage systems.

Citation Information

Patent Citations

  • Transition metal sulfide / graphene composite material, and preparation method and application thereof

    CN102760877A

  • Sodium-ion battery metal sulfide / graphene preparation method

    CN107017392A

  • Graphene-coated bimetallic selenide material and preparation method and application thereof

    CN110660981A

  • Sulfur-doped graphene-coated bimetallic sulfide composite material, preparation method and application of sulfur-doped graphene-coated bimetallic sulfide composite material in sodium-ion battery

    CN113346064A

  • Positive electrode material and preparation method thereof, positive plate and lithium-sulfur battery

    CN119153645A